Measurement Bases for Acquisitions and Mergers in Financial Accounting and in Commercial Law - Hana Vomáčková (European Financial and Accounting Journal, 2011)
In association with transactions involving businesses, acquisitions and mergers, etc., commercial law stipulates the new measurement of business assets and thus also net business assets. Similarly, financial accounting stipulates the new measurement of assets, liabilities and net assets with an impact on the amount and structure of equity. It is a principal question as to whether the new measurement bases required by both commercial law and financial accounting are in principal identical. Practice convinces us that the concepts provided in legislation (both commercial and accounting) differ in many cases and if a principle of precedence of the legal form over legal nature is applied, problems arise in respect to the main purpose of financial accounting, i.e. achieving a true and fair view. By stipulating the new measurement of business assets, commercial law intends to secure value objectivity of the relations between a company on the one side and its shareholders and statutory body members on the other (or between companies forming economic groups). Financial accounting focuses on new measurement at two levels: objective measurement on recognition – the acquisition of an asset, a group of assets or a business, or objective measurement as at the date of financial statements should the original measurement of the recognition of an asset or a liability would be significantly outdated and not reflective of the actual situation. It is essential that the discrepancies between the perspectives of commercial law and accounting legislation be analysed and removed in order to allow financial accounting to fulfil its basic purpose.
Keywords: M41; 650; Measurement base; Commercial law; Financial Accounting; Acquisition; Merger; Purchase method; Acquisition method; Uniting of interest method